2016
DOI: 10.1007/s12015-016-9694-0
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging of Ferumoxytol-Labeled Human Mesenchymal Stem Cells in the Mouse Brain

Abstract: The success of stem cell therapy is highly dependent on accurate delivery of stem cells to the target site of interest. Possible ways to track the distribution of MSCs in vivo include the use of reporter genes or nanoparticles. The U.S. Food and Drug Administration (FDA) has approved ferumoxytol (Feraheme® [USA], Rienso® [UK]) as a treatment for iron deficiency anemia. Ferumoxytol is an ultrasmall superparamagnetic iron oxide nanoparticle (USPIO) that has recently been used to track the fate of transplanted ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 54 publications
1
19
0
Order By: Relevance
“…Bos et al used MRI for tracking SPIONs-labeled MSCs transfused into the renal arteries and portal veins without any hazardous effect on the viability and differentiation of the injected cells [44]. Lee et al successfully used MRI to track ferumoxytol-labeled MSCs [45]. It was also shown that MSCs labeled with MRI-visible nanoparticles reduced the infarct volume of stroke [46].…”
Section: Discussionmentioning
confidence: 99%
“…Bos et al used MRI for tracking SPIONs-labeled MSCs transfused into the renal arteries and portal veins without any hazardous effect on the viability and differentiation of the injected cells [44]. Lee et al successfully used MRI to track ferumoxytol-labeled MSCs [45]. It was also shown that MSCs labeled with MRI-visible nanoparticles reduced the infarct volume of stroke [46].…”
Section: Discussionmentioning
confidence: 99%
“…Various methods have been developed for intravital imaging 54 . Studies have shown that although the most feasible method of MSC transplantation is through intravenous injection, in such conditions, most of the cells become trapped in the lungs 55 . Nevertheless, such entrapped MSCs can release microvesicles and immunomodulative factors and affect the overall state of the patient by modulating peripheral immune cells 56 .…”
Section: Mscs In Neurodegeneration and Brain Injury—preclinical Trialsmentioning
confidence: 99%
“…The surface markers used to characterize the human MSCs via fluorescence-activated cell sorting (FACS) are illustrated in Figure S2. Immunophenotyping was carried out by referring to previously reported procedures [56,57]. The MSCs used in this present study met the criterion set by the International Society for Cellular Therapy (ISCT) to define MSCs [58].…”
Section: Culture and Preparation Of Human Mscsmentioning
confidence: 99%